Nuclear applications in insect pest control: SIT for mosquitoes, vectors of human diseases - Yamada, Hanano; Justus Liebig University Giessen (My University, 2023)
Mosquitoes are still the most significant killers on earth, as they transmit malaria and numerous arboviral diseases worldwide. Although significant efforts have been made to manage the spread and growth of mosquito vector populations, many conventional control tools have been proven ineffective, insufficient, or unsustainable, and alternative methods are needed to reach and maintain low vector densities to break the transmission cycle. The sterile insect technique (SIT) has been proposed as an additional tool to add to the area-wide integrated pest management (AW-IPM) strategy for the improved and sustainable management of mosquito vectors, as this technique has been shown highly effective against other insect pests by enabling total population control [1,2] The essential components of the SIT include the mass rearing of the target species, the selection and reproductive sterilization of males, and their inundatory release into the target population, where successful copulation with wild females results in no offspring and consequently decreases the population size in subsequent generations. Key factors that influence the males’ success in reducing the population size in the field include the level of sterility in the male mosquito and the biological quality and aptitude required for mating success once released [2]. Various methods have been used for achieving reproductive sterility in mosquitoes in the context of the sterile insect technique (SIT), such as the use of chemosterilants [3–9] or by modifying the insect’s DNA [10–16]. However, the dominant approach for the SIT for most insect species is sterilization by exposure to ionizing radiation [1]. Most commonly, 60Cobalt or 137Caesium irradiators have been used for this purpose. More recently, the suitability of self-shielded X-ray irradiators as an alternative for sterilizing mosquitoes has been investigated [17,18]. However, a thorough evaluation should be performed on alternative devices before recommendations for the SIT can be made. For the characterization of irradiators, including mapping the dose distribution in the irradiation chamber or the sample being irradiated, and for routine or experimental irradiation, dosimetry is an indispensable component of irradiation quality assurance. Therefore, a standardized, reliable dosimetry system is required for the work presented in this thesis and is the topic of the first chapter. In response to reports from numerous SIT projects aimed to manage mosquito vectors that provided highly variable results regarding doses needed to achieve at least 99% induced sterility in the males, various endogenous and exogenous factors that could affect dose-response in the mosquitoes were assessed. The results indicated that the strain’s geographic origin and pupal size did not affect dose-response. In contrast, pupal age, atmospheric conditions (hypoxia/anoxia), cold temperatures, irradiation dose rate, and sample preparation methods affected irradiation outcome. The realization following this series of experiments is that it will be logistically tedious to control for pupal age, and even more so to control the dissolved oxygen levels when irradiating large numbers of pupae in water. Thus, the focus of the studies shifted to irradiation at the adult stage to overcome these issues, develop improved, standardized protocols for mosquito sterilization, and investigate irradiation protocols that may improve sterile male quality. The final chapter of this work describes the application potential of an “off-the-shelf” blood X-ray irradiator as an alternative to self-shielded gamma irradiators for use in SIT programs. Careful dose rate measurements and dose mapping of the irradiation chamber showed an excellent dose uniformity and a sufficient processing capacity, capable of sterilizing 75 million adult Aedes mosquitoes week, proposing this technology a helpful tool and improvement for mosquitoes SIT programs in the future.
Nukleare Applikationen in der Schädlingsbekämpfung: SIT gegen Stechmücken, menschliche Krankheitsvektoren
Keywords: sterile insect technique; vector control; radiobiology; mosquitoes; ddc:500